Delayed and limited administration of the JAKinib tofacitinib mitigates chronic DSS-induced colitis - Seal, Rishav; Schwab, Lara S. U.; Chiarolla, Cristina M.; Hundhausen, Nadine; Klose, Georg Heinrich; Reu-Hofer, Simone; Rosenwald, Andreas; Wiest, Johannes; Berberich-Siebelt, Friederike (Frontiers in Immunology, 2023)
In inflammatory bowel disease, especially dysregulated T cells express pro-inflammatory cytokines. We re-evaluated in the chronic AOM/DSS-induced colitis model, resembling ulcerative colitis, whether and when treatment with the Janus kinase inhibitor ‘tofacitinib’ could be curative. Comparing two with three cycles of tofacitinib medication in drinking water – intermittent with the DSS induction – revealed that two cycles were not only sufficient, but also superior over the 3-x regimen. The two cycles of the 2-x protocol paralleled the second and third cycle of the longer protocol. T cells were less able to express IFN-γ and serum levels of IFN-γ, IL-2, IL-6, IL-17 and TNF were significantly reduced in sera, while those of IL-10 and IL-22 had increased upon the 2-x protocol. Likewise, the frequency and effector phenotype of Tregs enhanced. This was accompanied by normal weight gain, controlled clinical scores and restored stool consistencies. The general and histological appearance of the colons revealed healing and tissue intactness. Importantly, two phases of tofacitinib medication completely prevented AOM-incited pseudo polyps and hyper-proliferation of epithelia, which was in contrast to the 3-x regimen. This implies that initial IBD-induced cytokine expression is not necessarily harmful as long as inflammatory signaling can later be suppressed, whereas time-restricted treatment allows for anti-inflammatory and tissue-healing cytokine activities.